Spiritualitas Dalam Perspektif Agama-Agama: Sebuah Pencarian Titik Temu - Labib Marzuki Shobir (Indonesian Journal of Humanities and Social Sciences, 2020)
Religion carries an important aspect from which it functions as a vehicle for humans to act on how to carry out our lives in this world. This condition tends to bring religion to the exclusive side. In social life, religion used to have conditions where all structures were built properly. Basically, the "major religions" (Judaism, Christianity and Islam) are derived from the same line. Tawhid is an example of this derivation, apart from the universal values that inherently arise from these religions. From this point of view, it can be said that religions have actually carried a linear character from one another.